Pengaruh Debt To Equty Ratio dan Earning Per Share Terhadap Return Saham dengan Kebijakan Deviden sebaga Intervening - Novita Anismawati (Universitas Widyatama, 2019)
This study aims to determine the effect of Debt To Equty Ratio dan Earning Per Share on stock returns with dividend policy as competitive. Sempel which was taken in the Main Industry and Kima companies. Data analysis method uses multiple linear regression tests. Der and eps have an influence on dividend policy, and der and eps have an influence on stock returns through dividend policy as intervening.